ANALISIS PENGARUH PELATIHAN TERHADAP KINERJA PERSONIL PADA SATUAN DETASEMEN KHUSUS 88 ANTI TEROR POLDA PAPUA - Leonard J.F. Kbarek; Gyberth Sitanala (STIE Pelita Nusantara Semarang, 2011)
Training programs is short and long-term training programs. This is a program that has been implemented by AT Papua Police Detachment 88, and can run properly. Although sometimes have experienced systematic problems in terms of funding and location of the easternmost region of Indonesia.Training of personnel is very influential on the performance of AT Papua Police Detachment 88, the data on the effect of training on performance as contained in the table are cumulative data of respondents who found the answer 73% of the samples taken were 30 personnel, who said the training is very influential.In terms of discipline, achievement, and work ethic, and training considered to be very effective to be used as benchmarks for Detachment 88 AT specifically in relation to the duties and functions of AT Detachment 88 police jurisdictions in the area of Papua.